Physical Therapy Patient Satisfaction at General Hospitals in Tripoli - Mohammed Wali,; Rashad Grera,; Moad Aljundi,; Amina Bashir, (AlQalam Journal of Medical and Applied Sciences, 2025)
Patient satisfaction has become a critical metric in healthcare delivery, as it reflects the quality of care and alignment with patient needs. In physiotherapy, patient opinions are integral to evidence-based practice along with clinical expertise and research evidence. This study aimed to assess the satisfaction levels of patients receiving physiotherapy services in general hospitals across Tripoli. A cross-sectional study was conducted involving 70 participants (30 males, 40 females) aged 19–65 years, recruited from physiotherapy units in four hospitals in Tripoli. A physical therapy satisfaction questionnaire was used to evaluate patient satisfaction across various dimensions of service quality. Statistical analysis was performed to identify significant differences in the satisfaction levels. of the participants, 42.9% were male, and 57.1% were female. The findings revealed statistically significant differences in most satisfaction-related items, with p-values less than 0.05, except for 18 items for which differences were not statistically significant (p > 0.05). Overall, most patients expressed high satisfaction with physiotherapy services, including the quality of care provided by therapists, the efficiency of services, and the effectiveness of treatment sessions. This study demonstrates that patients receiving physiotherapy services in public hospitals in Tripoli are generally satisfied with the care they receive. These results underscore the competence of public physiotherapy services and their ability to meet patient expectations regarding various aspects of care delivery. This study provides evidence to support the effectiveness and quality of public healthcare facilities in Tripoli.